Stroke Prevention With Direct Oral Anticoagulants (Doac) Versus Warfarin In Patients With Non-Valvular Atrial Fibrillation (Nvaf): A Real-World Cohort Meta-Analysis - Rizqiana Arum Sari; Habib Laksmana Prima; Delta Iswara; Faishal Hanif (International Journal of Health Engineering and Technology, 2026)
Atrial fibrillation, particularly NVAF, is a major risk factor for stroke and systemic embolism, yet real-world evidence on the effectiveness and safety of DOACs versus warfarin remains limited. This systematic review and meta-analysis compared the effectiveness and safety outcomes of direct oral anticoagulants (DOACs) vs for stroke prevention in patients with NVAF. This review followed PRISMA guidelines. Cohort studies published in the past 10 years were identified from PubMed, Scopus, and Google Scholar, with study quality assessed using the Newcastle–Ottawa Scale. Pooled hazard ratios for the effectiveness and safety of DOACs versus warfarin in NVAF were calculated using a random-effects model in RevMan 5.4.1. A total of 12 studies were included in this meta-analysis. Compared with warfarin, DOACs significantly reduced the risk of stroke or systemic embolism (HR = 0.76, 95% CI: 0.67–0.87), ischemic stroke (HR = 0.70, 95% CI: 0.54–0.92), and hemorrhagic stroke (HR = 0.62, 95% CI: 0.45–0.86). All-cause mortality was numerically lower with DOACs but not statistically significant (HR = 0.82, 95% CI: 0.66–1.01). For safety outcomes, DOACs were associated with a lower risk of major bleeding (HR = 0.81, 95% CI: 0.65–1.00) and intracranial hemorrhage (HR = 0.57, 95% CI: 0.50–0.65), while gastrointestinal bleeding did not differ significantly between groups (HR = 1.09, 95% CI: 0.62–1.90). Based on real-world cohort evidence, DOACs demonstrate superior effectiveness in reducing stroke and systemic embolism and a more favorable safety profile compared with warfarin in patients with NVAF.